Comparison of extrapolated and interpolated temperature scales from 1000 °C to 2500 °C between a national measurement institute and an ISO17025 accredited calibration laboratory. (December 2015) - Lowe, Dave; Broughton, Mick; Machin, Graham; Willmott, Jon R.
Abstract: The current high temperature part of the international temperature scale of 1990 (ITS-90) is based on extrapolation from a reference fixed point, using Plancks law in ratio form. However in the near future the mise en pratique for the definition of the kelvin will also allow an interpolated thermodynamic scale based on high temperature references whose temperatures are known a priori. Both approaches to dissemination will be considered equally valid. A transfer radiation thermometer specifically designed with the dissemination to industry of a temperature scale based on the mise en pratique -kelvin approach has been constructed. It was calibrated at a national measurement institute and used to compare the two possible realisation schemes (i.e. radiation thermometer calibrated to ITS-90, and the same thermometer calibrated using high temperature references) to the local ITS-90 scale at an accredited industrial calibration laboratory. All the scales agreed within their respective uncertainties. It was found that the interpolation scheme could significantly reduce the uncertainties in a calibration laboratory without the full cost of maintaining ITS-90.